2016
DOI: 10.1111/ajr.12279
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cholangiogram during laparoscopic cholecystectomy: A clinical trial in rural setting

Abstract: The majority of patients treated in our centre were women, middle-aged patients booked for elective laparoscopic cholecystectomy. Although only 6.7% cases were suspicious for CBD stones pre-operatively, a total of 17% of patients with routine IOC suggested CBD stones. IOC was found to be safe, taking only an additional 28 min of total theatre time. Routine rather than selective use of IOC could be considered to improve patient safety and long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Out of 11 cases with history of obstructive jaundice, 9 cases showed negative IOC and 2 cases showed positive IOC. This was coincide with other study as in [7] in which IOC showed poor correlation between pre-operative suspicion and confirmed CBD stones (two patients only with preoperative suspected CBD stone confirmed on IOC and ERCP). In [6] IOC showed normal biliary tree anatomy with free flow of contrast into the duodenum in 87% of cases, while in 13% of cases IOC showed dilated CBD with free flow of the contrast into the duodenum but with no evidence of filling defects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Out of 11 cases with history of obstructive jaundice, 9 cases showed negative IOC and 2 cases showed positive IOC. This was coincide with other study as in [7] in which IOC showed poor correlation between pre-operative suspicion and confirmed CBD stones (two patients only with preoperative suspected CBD stone confirmed on IOC and ERCP). In [6] IOC showed normal biliary tree anatomy with free flow of contrast into the duodenum in 87% of cases, while in 13% of cases IOC showed dilated CBD with free flow of the contrast into the duodenum but with no evidence of filling defects.…”
Section: Discussionsupporting
confidence: 92%
“…Reports of timing for IOC vary based on technique, experience with the procedure, and setting [6] mentioned that IOC time ranged from 17 to 42min with mean time of 24.82min while in [7] IOC added an average of 28 minutes to total operative time. In [8] IOC time was just over 10 minutes, and in [9] IOC time ranged only from 2 to 16 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In such patients, intraoperative cholangiography (IOC) helps to delineate biliary tree anatomy, prevent bile duct injury and image stones in the CBD, although the routine use of IOC in LC remains a contentious issue. [6] The anomaly presented in the above case report has not been described previously in literature. The need of knowing and understanding of the anatomical variations of the extrahepatic biliary tree cannot be under-stressed!…”
Section: Discussionmentioning
confidence: 82%
“…After the third month, none of the patients had abdominal pain, jaundice, pancreatitis, cholangitis, abnormal LFTs, or was readmitted. A recent study showed that patients who had IOC had no readmissions after the surgery (26) . Khan et al (19) compared between those who had IOC and those who had not, and found that readmission rate was much higher in the latter group (0% vs. 4%) attributing readmission to abdominal pain and symptoms suggestive of CBD obstruction.…”
Section: Discussionmentioning
confidence: 99%